(untitled) (Baghdad Science Journal, 2012)
The objective of study is to investigate the effect of using of Whey – Extracted Soyamilk indifferent Proportions instead of Cow s milk on Standing Height of Muffin of 5.5 cm. was reached in the treatment C ( 50% Whey – Extracted Soyamilk ) as compared with a Control treatment A (0% Whey – Extracted Soyamilk) at which the Muffin height reached 4.8 cm. About the sensory evaluation , The results showed for the Flavour property , to a significant difference was found between the treatment A (0% whey – Extracted Soyamilk ) which got 6.2 degree as compared with the two treatments namely , D(75% Whey – Extracted Soyamilk) and E(100% Whey – Extracted Soyamilk) Which got 5.7 and 5.3 degree , respectively. For General Acceptance property , both treatments , B(25% Whey – Extracted Soyamilk) and C(50% Whey – Extracted Soyamilk) got 6.2 and 6.3 degree, respectively, as compared with treatment A(0% Whey – Extracted Soyamilk) which got 6.1 degree. Finally , from the above results it can be deduced that treatments C and B were the best selective treatments from the stand points of nutrition value and quality properties of Muffin.